Cyst of the gastric wall arising from heterotopic pancreas: report of a case - Cecchini, Stefano; Marchesi, Federico; Caruana, Pietro; Tartamella, Francesco; Mita, Maria teresa; Rubichi, Francesco; Roncoroni, Luigi (Acta Biomedica Atenei Parmensis, 2016)
Heterotopia of pancreatic tissue is a common developmental anomaly, affecting predominantly the gastrointestinal tract. The case of a symptomatic cyst arising from the posterior gastric wall in a 40-year-old man is presented, undergoing laparoscopic gastric wedge resection. Pathology report described a cyst of the gastric wall lined by ductal pancreatic epithelium.